INTERAKSI SOSIAL WARGA PENGANUT AGAMA HINDU DENGAN WARGA PENGANUT AGAMA BUDHA PASCAKONVERSI AGAMA DI DESA PAKRAMAN PETANDAKAN KABUPATEN BULELENG - Darmayoga Kantina, I Komang Agus; Suka Arjawa, I Gst Putu Bagus; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
This thesis is collected because of the religion conversion by some citizens of Petandakan Village and has been long time. In the long time of that process usually the pattern of relations between people which has different religions get dynamics experience. The dynamics relation sometimes has harmonious characteristic, but there is certainly leads to, jealousy, and even conflict. This research has a problem formulation (1) how the pattern of society interaction after religion conversion, (2) how the implication that happened in conversion society, (3) what is the meaning of religion conversion for Buddhist citizens. The discussion of this research found that the pattern of interaction between Hindu and Buddhist residents is associative and dissociative. While the post-conversion implications of Buddhist residents are they build temples and cemeteries, the lease system applies to people living in village, unequal inheritance division. Then the meaning of religious convention is Buddhists can run the dana, sila, dipa, and meditation to find the highest happiness in their lives. The conclusions from the results of interactions research that are associative and dissociative among the citizens, and also there are implications of a positive and negative and religious significance and social meaning that occurs in the adherents of Hinduism with Buddhism. Keywords: Hinduism, Buddhism, Religious Conversion, and Social Interaction